The Role of Teacher Health and Work Environment on Teacher Certification Through Leader Image - Husna, Yayah Nihayatul (Penerbit Goodwood, 2025)
Purpose: This study aims to develop a new model identifying factors that directly or indirectly influence teacher certification, focusing on the roles of teacher health, work environment, and leader image. Research methodology: A quantitative research approach was employed by distributing questionnaires to certified ASN teachers. The study population comprised 388 certified teachers in Serang City, with a sample of 80 respondents selected through purposive sampling. Data were analyzed using the Structural Equation Model with Partial Least Squares (SEM/PLS) to test both direct and indirect effects among variables. Results: Findings revealed: (1) Teacher health has no direct effect on teacher certification; (2) Work environment significantly influences teacher certification; (3) Teacher health does not significantly affect leader image; (4) Work environment significantly affects leader image; (5) Leader image significantly influences teacher certification; (6) Teacher health significantly affects teacher certification indirectly through leader image; and (7) Work environment significantly affects teacher certification indirectly through leader image. Conclusions: Teacher certification is strongly influenced by the work environment and leader image, both directly and indirectly, while teacher health exerts an indirect effect through leader image. This highlights the central role of organizational conditions and leadership perception in improving teacher certification outcomes. Limitations: The study is limited by a small sample size and restricted to certified teachers in Serang City, limiting the generalizability of the findings. Contribution: This research underscores the importance of improving the work environment and leader image to strengthen teacher certification programs.